Breeding biology of Fairy Terns on Magone Islet, New Caledonia. (1st October 2020) - Villard, Pascal; Hunt, Gavin; Coll, Jonathan; Cassan, Jean-Jérome
ABSTRACT: The threatened Fairy Tern ( Sternula nereis ) is separated into three sub-species: S. n. nereis in Australia, S. n. davisae in New Zealand and S. n. exsul in New Caledonia. Poor breeding success was noted in S. n. exsul but the factors responsible were little known. To address this knowledge gap we documented the breeding biology in a small colony on mammal-free Magone Islet off the west coast of mainland Grande-Terre. We monitored the colony daily for 215 hours over 68 days in 2018. The clutch size varied from 1–3 eggs and incubation lasted 22.5 days. Overall breeding success was 14.8% (8 chicks fledged from 54 eggs), with egg/chick mortality due to a range of factors, including egg failure/chick death, tidal flooding, avian predation and desertion. Further work is needed to determine the impact human-associated disturbance has on S. n. exsul breeding colonies. In the meantime, the sub-species' vulnerable status requires restriction of human access to islands where these colonies are established.